Intraperitoneal Administration of a Developed Targeted Brain Prodrug of Ibuprofen - Alkrad, Jamal Alyoussef (Asian Journal of Pharmaceutics (AJP), 2020)
Introduction: The efficiency of using ibuprofen for protecting the brain against Alzheimer’s disease can be improved by developing a prodrug of ibuprofen able to distribute better through the blood–brain barrier (BBB). Materials and Methods: In this study, the hydroxyethyl ibuprofen (HEI) was synthesized as a prodrug by esterification of ibuprofen sodium through 2-bromoethanol then characterized using proton nuclear magnetic resonance and mass spectroscopy. The hydrolysis of HEI was evaluated in phosphate buffer at different pH values. Furthermore, the conversion of the prodrug to the parent drug was studied in vitro in rat’s brain homogenates and plasma. Moreover, the kinetics of the HEI was studied in rats after intraperitoneal application in comparison to intraperitoneal injected ibuprofen. Results: The stability of HEI in buffer solutions decreased with increasing pH value. On the other hand, it was hydrolyzed rapidly in rat’s plasma and faster than in brain homogenates. HEI was detected in plasma at low concentration for short time where it did not appear in brain. Hence, HEI is hydrolyzed in plasma to ibuprofen; the kinetic parameters of HEI were estimated by quantifying resulted ibuprofen. The bioavailability, absorption rate, and elimination rate constants of the prodrug were lower in plasma as well as in brain than of the parent drug. Furthermore, they were lower of both prodrug and parent drug in brain than in plasma. Discussion and Conclusions: The diffusion rate of the drug and prodrug into plasma and brain was dependent on the peritoneum membrane and BBB characteristics besides to the difference of the polarity between HEI and ibuprofen.